The Siren Song of the graphic Arts: The involvement of 17th-century Antwerp history painters with printmaking - Diels, Ann (In Monte Artium, 2010)
Abstract Like their contemporary Peter Paul Rubens, a few Antwerp history painters showed some interest in the graphic medium. They committed engravers for long periods or projects of limited duration to engrave their designs. The bulk of their designs for prints were specifically created for engravings, only a relatively small number of prints reproduced their paintings. Thus the serving role of the prints in 17th century Antwerp may not be overestimated. In the first place, prints seem to have been independent artistic creations (whether visual support tools to texts: e.g. book illustrations). The initiative for the publication of reproductive prints was often not taken by the painters themselves, but rather by print publishers, engravers, institutions or individuals.